Mechanisms underlying the low-temperature adaptation of 17β-estradiol-degrading bacterial strain Rhodococcus sp. RCBS9: insights from physiological and transcriptomic analyses - Li, Qiannan; Pan, Hanyu; Hao, Peng; Ma, Zhenhua; Liang, Xiaojun; Yang, Lianyu; Gao, Yunhang (Frontiers in Microbiology, 2024)
The 17β-estradiol (E2)-degrading bacterium Rhodococcus sp.RCBS9 previously showed remarkable resistance to the combined stresses of low temperature and E2. In this study, physiological experiments and transcriptomic analysis were performed to investigate the mechanisms underlying the strain's low-temperature adaptation and briefly analyze how it maintains its ability to degrade E2 at low temperature. The results showed that the strain's signal transduction functions, adaptive changes in cell membrane and cell wall structure, gene repair functions, and synthesis of antioxidants and compatible solutes are key to its ability to adapt to low temperature. In addition, its stress proteins in response to low temperature were not typical cold shock proteins, but rather universal stress proteins (USPs) and heat shock proteins (HSPs), among others. The strain also upregulated biofilm production, transporter proteins for carbon source uptake, and proteins for fatty acid degradation to ensure energy generation. The strain's multiple stress responses work synergistically to resist low-temperature stress, ensuring its adaptability to low-temperature environments and ability to degrade E2. Finally, six genes related to survival at low temperature (identified in the transcriptome analysis) were expressed in E. coli BL21, and they were found to contribute to recombinant E. coli growth at low temperature.